(untitled) (Latakia University (formerly Tishreen) Journal for Research and Scientific Studies - Arts Humanities Series, 2026)
This research examines the emotional values in the poetry of Nadim Muhammad from an aesthetic perspective, through the analysis of four basic values that form the core of the emotional experience in his texts, namely: love, pain, life, and death. It aims to reveal how these values ​​manifest in his poetry and their role in expressing the poet’s vision of existence and humanity. Love emerges as a central theme in Nadeem Muhammad’s poetry, appearing as a driving force that gives life meaning and alleviates the harshness of reality. Pain, on the other hand, is presented as an experience through which the poet reflects his personal suffering, lending the text a profound human dimension. As for the value of death, it is not presented merely as an end, but as an existential reality that provokes questioning and contemplation, linked to the search for meaning and immortality. Meanwhile, life in his poetry represents a space of struggle. The research followed the descriptive approach, benefiting from the procedures of aesthetic criticism in approaching the text to reach an integrated aesthetic vision in its cognitive revelations, and came out with results, the most important of which is that emotional values ​​reveal a contemplative tendency that leads to a coherent emotional unity in the poetic text.